Fundamental understanding of the corrosion and biomineralization of MgO surfaces – An in situ AFM study - Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Corrosion Science)

Low-aspect ratio nanopatterns on bioinert alumina influence the response and morphology of osteoblast-like cells - Wittenbrink, Isabel; Hausmann, Anne; Schickle, Karolina; Lauria, Ines; Davtalab, Roswitha; Foss, Morten; Keller, Adrian; Fischer, Horst (Biomaterials)

On the way to identify microorganisms in drinking water distribution networks via DNA analysis of the gut content of freshwater isopods - Mayer, Michael; Keller, Adrian; Szewzyk, Ulrich; Warnecke, Hans-Joachim (Journal of Biotechnology)

Fundamentals and Applications of Reflection FTIR Spectroscopy for the Analysis of Plasma Processes at Materials Interfaces - Grundmeier, Guido; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Plasma Processes and Polymers)

Spectroscopic and Microscopic Investigations of Degradation Processes in Polymer Surface-Near Regions During the Deposition of SiOx Films - Mitschker, Felix; Dietrich, Jan; Ozkaya, Berkem; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Awakowicz, Peter; Grundmeier, Guido (Plasma Processes and Polymers)

Characteristics of a propagating, self-pulsing, constricted ‘γ-mode-like’ discharge - Schröder, Daniel; Burhenn, Sebastian; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, Volker (Journal of Physics D: Applied Physics)

Note: Ion-induced secondary electron emission from oxidized metal surfaces measured in a particle beam reactor - Marcak, Adrian; Corbella, Carles; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Review of Scientific Instruments)

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)